Trends in Neonatal Dysphagia Research: Insights From a Text Mining Approach. - Krishnamurthy, Rahul; Balasubramanium, Radish Kumar; Kamath, Nutan; Bhat, Kamalakshi G. (Canadian Journal of Speech-Language Pathology & Audiology, 2020)
Meta-research is an emerging field that can provide valuable insights into research trends. This preliminary meta-research study aimed to trace and describe the research patterns in the area of neonatal dysphagia from 1970 to present using the technique of text mining. It also aimed to compare the amount of published research in the last 5 decades, identify journals that published the most research papers on neonatal dysphagia, and provide insights into the most common research topics. We utilized a combination of text mining and bibliometric-scientometrics techniques. The titles and abstracts of various scientific articles were analyzed for word frequency and relationship between them using hierarchical cluster analysis and co-occurrence network techniques. A total of 1819 research articles were published across various journals under the Scopus database. Research themes centred around feeding problems in neonates, clinical evaluation, and management, and a few studies focused on treatment outcomes. Findings of this study emphasize the need for unification of terminologies, wider adaptation of the International Classification of Functioning, Disability, and Health framework (World Health Organization, 2001), interprofessional education, and more evidence to support the practice of neonatal dysphagia.